Rynek ubezpieczeń finansowych w Polsce w latach 2003-2005 - Ciuman, Krystyna (The Market of Financial Insurance in Poland in the Period 2003-2005, 2008)
This paper analyses the characteristic of the market of financial insurance: credit insurances, suretyships, and insurances of various financial risks. The analysis is based on the following criteria: - the availability of financial insurances, - the size of insurance premiums, - the outward reinsurance in financial insurances, - technical accounts of financial insurances.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 46-53